Are adult mentalizing abilities associated with mind-mindedness? - Barreto, Ana Luisa (2016)
The precise nature of the relation between adult mentalizing abilities and parental representations of the child as a mental agent (mind-mindedness) is under current debate. While some authors state that it is the same competence expressed in different contexts, others assert that they are different constructs. This study examined the relation between mentalizing and mind-mindedness, in mothers and fathers, while investigating their potential links to socio-demographic, parental, and child variables. Participants were 74 families comprising of mother, father, and their preschool-aged child. Controlling for educational level, psychopathological symptoms, and children's reported temperament, the relation between mentalizing and mind-mindedness was non-significant. Moreover, mentalizing and mind-mindedness were shown to have distinct correlates, supporting the proposal that they are two distinct constructs.